PENERAPAN STRATEGI EVERYONE IS A TEACHER HERE (ETH) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 003 BINABARU KAMPAR KIRI TENGAH - Amiati, Vira Eka; Antosa, Zariul; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the problem of low learning result of IPS student of class III SDN 003 Binabaru Kampar Kiri Tengah. Where of the 24 students only 8 students who achieved the KKM value set by the school that is 75 for subjects IPS, with grade average grade of 60.83. Based on these problems, researchers apply ETH strategy to improve the learning process. The results of data analysis obtained the average value of daily replication cycle I 71.25, an increase of 17.12% of the basic score. Continued in cycle II the average daily repetition of students has increased again to 80.42. Before applied ETH strategy of student's classical completeness is 33,34%, then after applied ETH strategy on cycle I the total number of student which is complete up to 66,67% and in cycle II it has increased again to 87,50%. The increase in learning outcomes is supported by teacher and student activity where in the first meeting the teacher gets a 62.50% sufficient category percentage and the second meeting is 70.83% enough category. The first meeting of cycle II increased to 87.50% and the second meeting was 93.83% very good category. The percentage of first cycle student activity in first cycle was 54,16% less category once. second meeting 70,83% enough category and at first meeting of cycle II increased to 83,33% good category, second meeting 87,50% very good category. From this research, it can be concluded that the implementation of ETH strategy can improve the learning result of IPS student of class III SDN 003 Binabaru Kampar Kiri Tengah.Key word: everyone is a teacher here (ETH), IPS learning result